Magnesium alloy with electromagnetic shielding and heat and corrosion resistance enhanced by substrate microstructure-multiplex conversion film and preparation method thereof

CN122879689APending Publication Date: 2026-10-09JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611067782.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明的目的在于针对现有技术中转化膜创新性不足、MXene/Ag复合体系界面不稳、气凝胶封闭层创新点单一等问题,提供一种基体组织-多元转化膜协同增强电磁屏蔽、耐热耐蚀镁合金及其制备方法

Benefits of technology

[0110]综上可知,本发明的性能提升并非来源于单一工艺步骤,而是来源于各层级结构之间的显著协同作用:经均匀化、热挤压和固溶-时效处理后的耐热镁合金基体为后续膜层提供了稳定且有利于成核的组织基础;多元稀土复合转化膜提高了膜/基界面结合力并提供初级耐蚀防护;MXene/Ag复合导电网络层显著增强了电磁屏蔽能力;TMCS-改性疏水SiO2气凝胶热障封闭层进一步发挥隔热、疏水抗渗和缺陷封闭作用。四者协同作用,使镁合金由传统单一表面阻挡型防护提升为兼具组织强化、界面稳固、电磁屏蔽和热障隔离的多级复合防护体系,体现出显著的技术进步和实际应用价值。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a substrate structure and a multi-element conversion film synergistically enhanced electromagnetic shielding, heat-resistant and corrosion-resistant magnesium alloy and a preparation method thereof, and belongs to the technical field of magnesium alloy surface protection. The Mg-Al-Si-Ca-Zn heat-resistant magnesium alloy is used as a base material, and after homogenization, low-speed hot extrusion and solid solution-aging heat treatment, a Ce / La / Sm ternary rare earth phytic acid nucleation layer and a Y-Mo-P-V-Zr / BTA multi-component stability-enhancing layer are prepared by stepwise immersion, and a multi-element rare earth composite conversion corrosion-resistant bottom layer is obtained by densification of phosphate. x MXene, a DDT modified nano-silver and KH550 modified Ti3C2T MXene composite electrophoretic liquid, and a MXene / Ag composite conductive shielding layer is deposited; finally, a silane coating heat barrier hole sealing is performed on the SiO2 aerogel powder doped with TMCS. The application relies on the synergistic effect of substrate structure regulation and four-layer composite protection system, and the 1mm magnesium alloy plate has an electromagnetic shielding efficiency of not less than 95dB at 1GHz, and a stable heat-resistant time of not less than 6h at 300 DEG C, and simultaneously has excellent corrosion resistance, and can be widely applied to the integrated protection of magnesium alloy structural parts serving in high temperature in the fields of aerospace, 5G communication and new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of multifunctional magnesium alloy matrix preparation and surface protection technology, specifically relating to a magnesium alloy with synergistic enhancement of electromagnetic shielding, heat resistance, and corrosion resistance through matrix microstructure and conversion film, and its preparation method. More specifically, it relates to a method for preparing a magnesium alloy with both heat resistance, corrosion resistance, and electromagnetic shielding properties by controlling the microstructure of a heat-resistant magnesium alloy matrix containing Al, Si, Ca, and Zn through low-speed hot extrusion and heat treatment, and sequentially constructing a multi-element rare earth + multi-anion composite conversion film, a thiol-modified Ag / silane-modified MXene composite conductive network layer, and a TMCS-modified hydrophobic SiO2 aerogel thermal barrier sealing layer on its surface. Background Technology

[0002] Magnesium alloys possess advantages such as low density, high specific strength, high specific stiffness, excellent damping and vibration reduction performance, and ease of recycling, making them one of the important metallic materials for achieving lightweight components in aerospace, electronic communications, and new energy vehicles. They show great application potential, especially in applications requiring a balance between weight reduction, structural load-bearing capacity, electromagnetic compatibility, and high-temperature service stability. However, magnesium alloys are chemically reactive, have low standard electrode potentials, and are prone to corrosion in humid, saline, or multi-temperature cycling environments. Furthermore, at higher temperatures, they are susceptible to grain coarsening, second-phase aggregation, or decreased microstructural stability, leading to a decline in mechanical properties, corrosion resistance, and service reliability. In addition, ordinary magnesium alloys have limited electromagnetic shielding capabilities, and their surface protective layers are prone to cracking, peeling, or failure in high-temperature environments. These issues collectively limit the further widespread application of magnesium alloys in complex service environments.

[0003] To improve the overall performance of magnesium alloys, existing technologies typically employ the following modification approaches: First, controlling the matrix microstructure through heat treatment, extrusion, etc., to refine grains, uniformly distribute the second phase, and improve matrix strength and thermal stability; second, using chemical conversion films, anodic films, or organic sealing layers to improve corrosion resistance; third, introducing conductive metallic fillers, carbon-based materials, or two-dimensional conductive sheets to construct electromagnetic shielding layers; and fourth, utilizing aerogels, ceramic fillers, or heat-resistant organosilicon systems to form thermal insulation sealing layers to enhance thermal barrier capabilities. However, existing technologies still have the following shortcomings: matrix microstructure control and surface film construction are disconnected; traditional rare earth conversion films have relatively simple compositions, resulting in insufficient interfacial stability and high-temperature corrosion resistance; the construction methods of conductive shielding layers lack stability; and existing thermal barrier sealing layers have limited functionality and insufficient synergy with underlying functional films. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies, such as insufficient innovation in conversion films, unstable interfaces in MXene / Ag composite systems, and limited innovation in aerogel sealing layers. This invention provides a matrix-multi-element conversion film synergistic enhancement of electromagnetic shielding, heat-resistant and corrosion-resistant magnesium alloys, and its preparation method. First, coarse second phases are controlled into heat-diffusing and stable Mg2Si and Al2Ca nanophases through low-speed hot extrusion and precise heat treatment. A multi-element rare-earth composite conversion film is constructed, with Ce / La / Sm stepwise nucleation and V-Zr-BTA cathode inhibition synergistically strengthening the interface. Pre-modified KH550-MXene and DDT-Ag form a stable, high-conductivity network through chemical bonding and interlocking. A TMCS-modified narrow-particle-size hydrophobic aerogel top layer forms a nanoporous labyrinth effect, blocking corrosive media penetration and providing thermal barrier protection. This creates a multi-level synergistic protection system, significantly improving the overall service performance of magnesium alloys in complex environments. This invention achieves a transformation in performance improvement mechanism from a single-dimensional surface barrier mechanism to an intrinsic matrix microstructure optimization and multi-level gradient synergistic defense mechanism.

[0005] To achieve the above objectives, the present invention adopts the following technical solution.

[0006] A method for preparing a magnesium alloy with synergistic enhancement of electromagnetic shielding and heat and corrosion resistance by matrix structure and conversion film, characterized by comprising the following steps:

[0007] 1. A method for preparing a magnesium alloy with synergistic enhancement of electromagnetic shielding and heat and corrosion resistance by matrix structure and conversion film, characterized by comprising the following steps:

[0008] (1) Prepare magnesium alloy matrix Mg-8Al-3Si-2Ca-1Zn (wt.%), and perform homogenization treatment, low-speed hot extrusion, solution treatment and aging heat treatment;

[0009] (2) After the magnesium alloy substrate is subjected to surface pretreatment of degreasing, pickling, activation and cleaning in sequence, a multi-element rare earth composite conversion film is prepared on the surface of the magnesium alloy substrate by step-by-step impregnation and then subjected to phosphate densification treatment:

[0010] S2.1 The magnesium alloy substrate is placed in the nucleation solution and immersed for 2-8 min to form a synergistic nucleation layer containing Ce, La, Sm ternary rare earth elements and phytic acid. Then, it is immersed in the stabilizing solution for 5-15 min to form a multi-anion stabilizing layer containing synergistic Y-Mo-PV-Zr and benzotriazole (BTA).

[0011] The nucleation solution contains: Ce(NO3)3·6H2O 0.010~0.030 mol / L, La(NO3)3·6H2O 0.020~0.060 mol / L, Sm(NO3)3·6H2O 0.005~0.015 mol / L, phytic acid 2~6 mL / L, H2O2 4~10 mL / L, and pH 4.5~5.5;

[0012] The stabilizing solution contains: Y(NO3)3·6H2O 0.005~0.020mol / L, Na2MoO4·2H2O 2~8 g / L, NH4H2PO4 5~15 g / L, NaVO3 0.5~2 g / L, K2ZrF6 0.5~3 g / L, benzotriazole (BTA) 0.2~1g / L, and pH 3.5~5.0;

[0013] S2.2 The phosphate densification treatment solution includes NH4H2PO4 and / or (NH4)2HPO4, with a mass concentration of 4.5% to 5.5%, a treatment temperature of 45 to 55°C, and a treatment time of 3 to 5 min;

[0014] (3) An MXene / Ag composite conductive network layer was constructed on the densified magnesium alloy surface by electrophoretic deposition:

[0015] S3.1 KH550 silane-modified MXene: Take Ti3C2T x The MXene dispersion was transferred to a mixed solvent of ethanol and deionized water at a volume ratio of 9:1, and γ-aminopropyltriethoxysilane (KH550) was slowly added dropwise. The mass ratio of KH550 to MXene was (1~5):1. The mixture was then refluxed under magnetic stirring at 60~70℃ for 4~8 h, allowing KH550 to chemically bond with the -OH / -F end groups on the MXene surface through a hydrolysis-condensation reaction, forming KH550-MXene with covalently grafted aminosilane. After the reaction was completed, the mixture was centrifuged and washed until neutral, and then freeze-dried under vacuum to obtain KH550 silane-modified MXene powder.

[0016] S3.2 DDT thiol-modified Ag nanoparticles: An ethanol solution of 1-dodecyl mercaptan (DDT) was added dropwise to Ag sol at a mass ratio of DDT to Ag of (0.05~0.20):1. The mixture was stirred at room temperature for 4~12 h to allow DDT to be stably coated on the Ag surface through strong Ag-S coordination bonds, forming DDT-Ag. After centrifugation, washing, and vacuum drying, DDT thiol-modified Ag nanoparticles were obtained.

[0017] S3.3 Electrophoretic Solution Preparation and Deposition: Weigh KH550-MXene and DDT-Ag at a mass ratio of (7~9):(3~1), disperse them in a mixed solvent of ethanol and deionized water with a volume ratio of 80:20~98:2, add PVP 0.05~0.2 g / L as a dispersion stabilizer, and sonicate to obtain a uniform and stable electrophoretic solution, wherein the total concentration of the KH550-MXene and DDT-Ag complex is 0.4~1.0 g / L; use the sample to be plated as the cathode and an inert electrode as the anode, and carry out electrochemical deposition at room temperature under magnetic stirring. After the electrochemical deposition is completed, take out the sample, rinse and dry it.

[0018] (4) A silane sealing agent doped with TMCS-modified hydrophobic SiO2 aerogel is used to perform thermal barrier sealing treatment on the magnesium alloy after the conductive network layer is deposited, forming a heat insulation and protection top layer.

[0019] S4.1: The hydrophobic SiO2 aerogel powder has a particle size D50 of 2~15 μm and is hydrophobically modified on the wet gel surface by trimethylchlorosilane.

[0020] S4.2 Preparation of the sealing solution: KH550 is used as the film-forming silane with a volume concentration of 5% to 8%. A mixed solution of ethanol and water with a volume ratio of 90:10 to 98:2 is used as the solvent. The pH is adjusted to 4.0 to 5.5 with acetic acid and hydrolyzed for 1 to 3 hours. TMCS-modified hydrophobic SiO2 aerogel powder with a mass fraction of 5% to 12% is added to the solution. The mixture is mechanically stirred or ultrasonically dispersed for 20 to 60 minutes to form the sealing solution.

[0021] S4.3 Impregnation and curing: Immerse the sample after depositing the conductive network layer into the sealing liquid, and impregnate it at 25~30℃ for 10~20min. Pull it out at a uniform rate of 1~3 cm / min. After pre-curing at 30℃ for 8~15min, raise the temperature to 120~140℃ at 3~7℃ / min and hold for 20~30min. Cool it in the furnace and age it at room temperature for 20~28h.

[0022] Further, the magnesium alloy contains 2-4 wt.% Si, 1-3 wt.% Ca, 7-9 wt.% Al, and 0.5-1.5 wt.% Zn, with the balance being Mg and unavoidable impurities; the preferred nominal composition is Mg-8Al-3Si-2Ca-1Zn (wt.%).

[0023] Further, in step (1), the homogenization treatment temperature is 440-460℃, and after holding for 18-24 h, it is cooled in the furnace to below 300℃ and then air-cooled to room temperature; the low-speed hot extrusion rate is 0.5-1 mm / s, the hot extrusion temperature is 350-380℃, and the hot extrusion ratio is 9:1 or 16:1; the solution treatment temperature is 440-460℃, and after holding for 1.5-3 h, it is water-quenched; the aging treatment temperature is 170-190℃, and after holding for 30-40 h, it is air-cooled to room temperature.

[0024] Further, in step (2), the nucleation solution contains Ce(NO3)3·6H2O at a concentration of 0.020 mol / L, La(NO3)3·6H2O at a concentration of 0.040 mol / L, Sm(NO3)3·6H2O at a concentration of 0.010 mol / L, phytic acid at a volume concentration of 4 mL / L, H2O2 at a volume concentration of 6 mL / L, pH 5.0, and an immersion time of 5 min; the stabilizing solution contains Y(NO3)3·6H2O at a concentration of 0.010 mol / L, Na2MoO4·2H2O at a concentration of 5 g / L, NH4H2PO4 at a concentration of 10 g / L, NaVO3 at a concentration of 1.0 g / L, K2ZrF6 at a concentration of 1.5 g / L, benzotriazole at a concentration of 0.5 g / L, pH 4.2, and an immersion time of 10 min. min; the phosphate densification solution was NH4H2PO4 with a mass concentration of 5%, the treatment temperature was 50℃, and the treatment time was 4 min.

[0025] Further, in step S3.1, the mass ratio of KH550 to MXene is 3:1; the reaction is carried out under magnetic stirring and reflux at 60℃ for 6 h; in step S3.2, the Ag sol is prepared by using AgNO3 as the silver source, PVP as the dispersant, and ascorbic acid or NaBH4 as the reducing agent to reduce and prepare nano-Ag particles with a particle size of 20~50 nm in an ethanol / water system; the mass ratio of DDT to Ag is 0.10:1, and the reaction is carried out under stirring at room temperature for 8 h.

[0026] Furthermore, to ensure repeatability for those skilled in the art, Ti3C2T x MXene preferably adopts the following standardized process: Ti3C2T in S3.1 xThe MXene dispersion was prepared by the following method: Using a corrosion-resistant polytetrafluoroethylene (PTFE) or polypropylene (PP) reaction vessel, an in-situ fluorination etching system was prepared by adding LiF to a hydrochloric acid solution under magnetic stirring. The hydrochloric acid concentration was 8–10 mol / L, and the amount of LiF added was 1.0–2.0 g / 20 mL of hydrochloric acid solution. Subsequently, Ti3AlC2 powder was slowly added, controlling the mass ratio of Ti3AlC2 to LiF to be 1:(1.2–1.5). The reaction was carried out at 30–45 °C for 30–40 h to selectively remove the Al layer. After etching, the slurry was transferred to a centrifuge and repeatedly washed with deionized water at a centrifuge speed of 4200–4800 rpm for 6–8 min per centrifugation, until the pH of the supernatant reached 6–7. The resulting precipitate was then redispersed in deionized water and ultrasonically peeled under ice bath conditions for 70–80 min to obtain a few-layer or monolayer Ti3C2T. x MXene dispersion; after peeling, centrifuge again at low speed and collect the supernatant for later use. Furthermore, to reduce the risk of oxidative deactivation, the obtained MXene dispersion is preferably stored at 4°C in the dark.

[0027] Further, in step S3.3, the mass ratio of KH550-MXene to DDT-Ag is 8:2; the total concentration of both in the electrophoresis solution is 0.8 g / L, the PVP concentration is 0.1 g / L, and the volume ratio of ethanol to deionized water is 90:10; the electrode spacing is 12~20 mm, a DC voltage of 25~35 V is applied for deposition for 8~12 min, the deposition solution temperature is controlled at 23~27℃, and the liquid is kept uniform by magnetic stirring at 100~250 rpm during deposition; after deposition, the sample is taken out, the undeposited particles are gently rinsed with ethanol, and dried at 65~75℃ for 35~45 min; preferably, the electrode spacing is 15 mm, a DC voltage of 30 V is applied for deposition for 10 min.

[0028] Further, in step (4), the volume concentration of KH550 in the sealing liquid is 6%, the volume ratio of ethanol to water is 95:5, the hydrolysis time is 2 h, the mass fraction of TMCS-modified SiO2 aerogel powder is 8%, the impregnation and curing conditions are impregnation at 25℃ for 15 min, the lifting rate is 2 cm / min, the pre-curing at 30℃ for 12 min, the temperature is increased to 130℃ at 5℃ / min and held for 25 min, cooled with the furnace, and aged at room temperature for 24 h.

[0029] Further, the TMCS-modified hydrophobic SiO2 aerogel is prepared by the following method: using tetraethyl orthosilicate and / or water glass as the silicon source and anhydrous ethanol as the solvent, a homogeneous SiO2 sol is obtained by acid-base two-step catalytic hydrolysis-condensation followed by stirring at room temperature for 1-1.5 h; the gel is allowed to stand for 8-16 h and then aged for 24-48 h to enhance the skeleton strength; after the aged wet gel is replaced with anhydrous ethanol 1-3 times, it is immersed in a TMCS / n-hexane mixture to carry out a silanization replacement reaction of the surface silanol groups, with a TMCS volume concentration of 5%-15%, a modification temperature of 50-70℃, and a modification time of 6-24 h, so that a large number of -OH groups on the gel surface are replaced by -OSi(CH3)3 to form a deep hydrophobic skeleton; the modified gel is dried at atmospheric pressure at 60-100℃ for 12-24 h, pulverized and sieved to obtain TMCS-modified hydrophobic SiO2 aerogel powder with a particle size D50 of 2-15 μm.

[0030] The nucleation solution described in this invention, based on the traditional Ce / La dual rare earth element, introduces a third rare earth element, Sm(NO3)3·6H2O. 3+ / Sm 2+ The redox potential is complementary to that of Ce and La, which can form multiple gradient nucleation sites on the highly active surface of the magnesium matrix, significantly reducing the critical supersaturation for nucleation and improving the film coverage; phytic acid (C6H 18 O 24 P6, as a polydentate phosphate organic ligand, chelates Mg through six phosphate groups. 2+ Al 3+ Rare earth ions form a highly dense coordination complex layer at the film / substrate interface, which can inhibit Mg... 2+ The dissolution process also serves as a chemical anchoring site for subsequent Y and P anions, greatly enhancing the chemical bonding between the conversion film and the substrate. H₂O₂, acting as a local oxidizing agent, promotes the transformation of rare earth ions from RE... 3+ It is transformed into a more stable oxide / hydroxide form. The stabilizing solution further introduces NaVO3 and V into the traditional Y-Mo-P system. 5+ As a highly efficient cathode-inhibiting corrosion inhibitor ion, it can react with Mg at the defect site. 2+ Insoluble magnesium vanadate is generated to plug micropores; K2ZrF6, Zr 4+The ZrO2 / ZrOF particles formed by hydrolysis can serve as a thermally stable reinforcing phase in the film, significantly improving high-temperature stability at 300℃, while F⁻ promotes activation and bonding. Benzotriazole (BTA), as an organic corrosion inhibitor, forms a dense protective complex layer with residual Cu / Fe impurities and Ag interfaces in the film through its triazole ring N atoms, significantly inhibiting the microgalvanic corrosion of Ag in the subsequent MXene / Ag layer. After final phosphate densification treatment, the resulting multi-element rare earth composite conversion film exhibits the characteristics of "three rare earth elements - multiple anions - organic / inorganic synergy," with significantly better film density, chemical bonding, and high-temperature corrosion stability than traditional single / binary rare earth conversion films.

[0031] In the process of KH550 silane grafting modification of MXene (KH550-MXene), the ethoxy groups of KH550 are hydrolyzed into active silanol groups, which are then reacted with Ti3C2T x The surface -OH and -F end groups undergo condensation, and the graft is stabilized through Si-O-Ti covalent bonds, introducing a large number of -NH2 active groups onto the surface. This modification significantly inhibits the oxidative deactivation of MXene, and the introduced -NH2 can form multiple hydrogen bonds / covalent bridges with the subsequent DDT-Ag and SiO2 aerogel top silane.

[0032] During the DDT thiol passivation of Ag nanoparticles (DDT-Ag), the DDT end group -SH self-assembles with the Ag surface through strong Ag-S coordination bonds to form a dense monolayer shell, effectively inhibiting the aggregation and migration between Ag particles and passivating the Ag surface activity, thereby reducing the risk of microgalvanic corrosion when in subsequent contact with the magnesium substrate.

[0033] During the electrophoretic deposition process of constructing the MXene / Ag composite conductive network layer, the positively charged (-NH2) surface of MXene and the relatively negatively charged (-S / -SH remnants and PVP) surface of DDT-Ag form electrostatic complementarity, and they adsorb to each other in the electrophoretic solution to form stable binary colloidal units. After deposition, a three-dimensional high-conductivity network of "lamellae MXene-spherical Ag interleaving" is formed, and Ag particles are tightly anchored to MXene-NH2 sites, effectively inhibiting Ag migration and aggregation.

[0034] During the process of modifying the hydrophobic SiO2 aerogel powder with TMCS, the active silanol groups on the surface of the gel skeleton are deeply replaced with a large number of trimethylsilyl-OSi(CH3)3, forming a uniform and dense hydrophobic layer. Compared with the traditional single gas / liquid phase modification of HMDS, the liquid phase modification of TMCS / n-hexane has the following advantages: (i) higher reactivity, which can achieve a near 100% replacement rate under milder conditions; (ii) n-hexane is a low-polarity solvent, which can protect the gel skeleton from capillary shrinkage during the drying process and significantly reduce the width of the pulverized particle size distribution; (iii) the reaction product HCl is easily volatilized with the solvent, leaving no alkaline byproducts. The modified gel is dried under high pressure (60~100℃, 12~24 h), pulverized and screened by airflow classification, and the particle size D50 is strictly controlled to be 2~15 μm. This particle size range can ensure good dispersibility and form a continuous and dense hydrophobic filler skeleton.

[0035] In the thermal barrier sealing layer, the surface of the SiO2 aerogel particles modified by TMCS is rich in -CH3 hydrophobic groups, which form a "hard core-flexible silicon-oxygen network" interlock with KH550 silane. The sealing layer has both thermal barrier insulation (aerogel nanopores scatter infrared / phonons) and superhydrophobic impermeability (preventing corrosive media from entering the underlying conductive network).

[0036] Compared with existing technologies, this invention improves the interfacial bonding between the magnesium alloy matrix and the film layer through the synergistic design of matrix structure regulation and multilayer composite film construction, and makes the resulting composite system have good corrosion resistance, electromagnetic shielding performance and thermal barrier insulation performance, while also having good high-temperature stability and application prospects. Specific implementation methods

[0037] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0038] The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy of the present invention includes the following steps:

[0039] (1) Prepare a heat-resistant magnesium alloy matrix containing Al, Si, Ca and Zn elements; first homogenize the magnesium alloy, then perform low-speed hot extrusion, and then perform heat treatment. By refining the grains and optimizing the distribution and deformation texture of the thermally stable phases of Mg2Si and Al2Ca, the interfacial mechanical bonding and chemical bonding strength between the multi-element rare earth composite conversion film and its upper conductive network layer and the matrix are improved.

[0040] The nominal composition of the heat-resistant magnesium alloy matrix is ​​Mg-8Al-3Si-2Ca-1Zn (wt.%), with the following mass percentages for each component: Al 8 wt.%, Si 3 wt.%, Ca 2 wt.%, Zn 1 wt.%, and the balance being Mg and unavoidable impurities. As an example, the composition of the heat-resistant magnesium alloy matrix can be as follows: Si content 2-4 wt.%, Ca content 1-3 wt.%, Al content 7-9 wt.%, Zn content 0.5-1.5 wt.%, and the balance being Mg and unavoidable impurities.

[0041] The homogenization treatment is performed at a temperature of 440–460℃, held for 18–24 hours, then furnace-cooled to below 300℃ and air-cooled to room temperature. The low-speed hot extrusion rate is 0.5–1 mm / s, the hot extrusion temperature is 350–380℃, and the hot extrusion ratio is 9:1 or 16:1. The solution treatment temperature is 440–460℃, held for 1.5–3 hours, and then water-quenched. The aging treatment temperature is 170–190℃, held for 30–40 hours, and then air-cooled to room temperature.

[0042] (2) The magnesium alloy substrate after hot extrusion and heat treatment is first subjected to conventional degreasing, pickling, activation and cleaning. Then, a multi-element rare earth composite conversion film containing Ce / La / Sm ternary rare earth + phytic acid nucleation layer and Y-Mo-PV-Zr-BTA stabilizing layer is prepared on its surface by step-by-step impregnation, and then phosphate densification treatment is performed.

[0043] The degreasing process involves immersing the magnesium alloy substrate in an alkaline degreasing solution at 50–60°C for 5–10 minutes. The degreasing solution contains 20–30 g / L NaOH, 10–20 g / L Na3PO4, and 5–15 g / L Na2SiO3. The pickling process involves immersing the substrate in an 8%–12% (w / w) HNO3 solution at room temperature for 50–70 seconds. After pickling, the substrate is rinsed with deionized water and then countercurrent rinsed. The activation process involves using a mixture of phosphoric acid and hydrofluoric acid, where the volume concentration of H3PO4 is 25–35 mL / L and the volume concentration of HF is 15–25 mL / L. The activation time is 40–60 seconds. After activation, the substrate is rinsed with deionized water and dried with cold air.

[0044] The nucleation solution contains: Ce(NO3)3·6H2O 0.010~0.030 mol / L, La(NO3)3·6H2O 0.020~0.060 mol / L, Sm(NO3)3·6H2O 0.005~0.015 mol / L, and phytic acid (C6H2O). 18 O 24 P6) 2-6 mL / L, H2O2 4-10 mL / L, pH 4.5-5.5.

[0045] The stabilizing solution contains: Y(NO3)3·6H2O 0.005~0.020mol / L, Na2MoO4·2H2O 2~8 g / L, NH4H2PO4 5~15 g / L, NaVO3 0.5~2 g / L, K2ZrF6 0.5~3 g / L, benzotriazole (BTA) 0.2~1g / L, and pH 3.5~5.0.

[0046] First, the magnesium alloy substrate is immersed in a nucleation solution for 2–8 min to form a synergistic nucleation layer containing Ce, La, Sm ternary rare earth elements and phytic acid. Then, it is immersed in a stabilizing solution for 5–15 min to form a multi-anionic stabilizing layer containing γ-Mo-PV-Zr and benzotriazole (BTA). The phosphate densification treatment solution includes NH4H2PO4 and / or (NH4)2HPO4 at a mass concentration of 4.5%–5.5%. The phosphate densification treatment temperature is 45–55℃, and the treatment time is 3–5 min.

[0047] (3) Pre-modified Ti3C2T x MXene and DDT thiol passivated nano-Ag, and then directly compounded into an electrophoretic solution in a certain proportion, followed by electrophoretic deposition to construct an MXene / Ag composite conductive network layer.

[0048] Among them, pre-modified Ti3C2T x MXene is made by grafting KH550 silane onto its surface. The specific method is as follows: Take Ti3C2T x The MXene dispersion was transferred to an ethanol / water (9:1 volume ratio) system, and γ-aminopropyltriethoxysilane (KH550) was slowly added dropwise. The mixture was then refluxed under magnetic stirring at 60-70°C for 4-8 h, allowing KH550 to chemically bond with the -OH / -F end groups on the MXene surface through a hydrolysis-condensation reaction, forming KH550-MXene with covalently grafted aminosilane. After the reaction was completed, the mixture was centrifuged and washed until neutral, and then freeze-dried under vacuum to obtain KH550 silane-modified MXene powder.

[0049] DDT thiol-modified Ag nanoparticles: An ethanol solution of 1-dodecyl mercaptan (DDT) is added dropwise to Ag sol, and the mixture is stirred at room temperature for 4-12 h to allow DDT to be stably coated on the Ag surface through strong Ag-S coordination bonds, forming DDT-Ag; then, after centrifugation, washing, and vacuum drying, DDT thiol-modified Ag nanoparticles are obtained.

[0050] (4) The magnesium alloy after the conductive network layer was deposited was subjected to thermal barrier sealing treatment by TMCS-modified hydrophobic SiO2 aerogel (D50 is 2~15 μm) doped with KH550 silane; and post-treatment and drying were carried out to obtain electromagnetic shielding, heat-resistant and corrosion-resistant multi-element rare earth composite conversion film coating.

[0051] The sealing solution uses KH550 as the film-forming silane with a volume concentration of 5%–8%, and a mixed solution of ethanol and water with a volume ratio of 90:10–98:2 as the solvent. The pH is adjusted to 4.0–5.5 with acetic acid and hydrolyzed for 1–3 h. TMCS-modified hydrophobic SiO2 aerogel powder with a mass fraction of 5%–12% is added to the solution, and the mixture is mechanically stirred or ultrasonically dispersed for 20–60 min to form the sealing solution.

[0052] The sample after depositing the conductive network layer is immersed in the sealing solution and soaked at 25~30℃ for 10~20 min. It is then pulled out at a uniform rate of 1~3 cm / min. After pre-curing at 30℃ for 8~15 min, the temperature is increased to 120~140℃ at 3~7℃ / min and held for 20~30 min. The sample is then cooled in the furnace and aged at room temperature for 20~28 h to complete the thermal barrier sealing treatment.

[0053] Example 1

[0054] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, then furnace cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 350℃ at a speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0055] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0056] A multi-element rare earth composite conversion membrane was prepared. The nucleation solution was prepared with Ce(NO3)3·6H2O 0.020 mol / L, La(NO3)3·6H2O 0.040 mol / L, Sm(NO3)3·6H2O 0.010 mol / L, phytic acid 4 mL / L, and H2O 26 mL / L, adjusted to pH 5.0. The stabilizing solution was prepared with Y(NO3)3·6H2O 0.010 mol / L, Na2MoO4·2H2O 5 g / L, NH4H2PO4 10 g / L, NaVO3 1.0 g / L, K2ZrF6 1.5 g / L, and BTA 0.5 g / L, adjusted to pH 4.2. The pretreated sample was immersed in the nucleation solution for 5 min, then in the stabilizing solution for 10 min to form a multi-element rare earth composite conversion membrane on the substrate surface. The sample was then placed in a 5.0% NH4H2PO4 solution and densified at 50°C for 4 minutes. After removal, it was cleaned and dried.

[0057] Fabrication of MXene / Ag composite conductive network layer. First, Ti3C2T... x MXene: 1 g of Ti3AlC2 was added to an etching system prepared with 1.5 g of LiF and 30 mL of 9 mol / L HCl. The etching was performed by magnetic stirring at 40 °C for 36 h. After etching, the supernatant was repeatedly washed by centrifugation with deionized water until the pH of the supernatant was approximately 6. The resulting precipitate was then redispersed in deionized water and ultrasonically exfoliated for 75 min under ice bath conditions. After low-speed centrifugation, the supernatant was collected to obtain a few-layer Ti3C2T. x MXene dispersion. Then, KH550 silane modification was carried out: Take the above MXene dispersion, so that the mass of MXene is 0.5g, add it to 100mL of ethanol / water mixed solvent with a volume ratio of 9:1, and slowly add 1.5g of KH550 dropwise, that is, the mass ratio of KH550:MXene is 3:1. Reflux reaction at 60℃ for 6h; after the reaction is completed, centrifuge and wash until neutral, and freeze dry under vacuum to obtain KH550-MXene.

[0058] Next, DDT-Ag was prepared: 100 mL of 0.02 mol / L AgNO3 ethanol / water solution was prepared, 0.5 g of PVP was added, and 0.04 mol / L ascorbic acid solution was added dropwise while stirring. The reaction was carried out for 30 min to obtain Ag sol. Then, 1-dodecyl mercaptan (DDT) ethanol solution was added dropwise, controlling the mass ratio of DDT:Ag to 0.10:1, and the mixture was stirred at room temperature for 8 h. After centrifugation, washing, and vacuum drying, DDT-Ag was obtained. Finally, electrophoretic deposition was performed: 0.064 g of KH550-MXene and 0.016 g of DDT-Ag were weighed, i.e., the mass ratio of the two was 8:2, and dispersed in 100 mL of ethanol / water mixed solvent with a volume ratio of 90:10. 0.01 g of PVP was added, and the mixture was sonicated for 40 min to obtain the electrophoretic solution. The total concentration of the complex was 0.8 g / L. Using the sample as the cathode and the graphite plate as the anode with an electrode spacing of 15 mm, deposition was carried out at a DC voltage of 30 V for 10 min. During the deposition process, the liquid was kept uniform by magnetic stirring at 200 rpm. After deposition, the sample was removed, the undeposited particles were gently rinsed with ethanol, and dried at 70 °C for 40 min to form an MXene / Ag composite conductive network layer.

[0059] A thermal barrier sealing layer of TMCS-modified hydrophobic SiO2 aerogel was prepared. First, TMCS-modified hydrophobic SiO2 aerogel powder was prepared by mixing TEOS, ethanol, and water in a volume ratio of 1:4:2.5. Hydrolysis was performed by adjusting the pH to 3 with hydrochloric acid, followed by polycondensation by adjusting the pH to 9 with ammonia. The mixture was stirred at room temperature for 1.2 h to obtain a homogeneous SiO2 sol. The sol was allowed to stand for 12 h to gel, and then aged for another 36 h. The wet gel was replaced three times with anhydrous ethanol, each time for 12 h. Then, the gel was immersed in a 10% TMCS / n-hexane mixture and modified at 60 °C for 12 h. The modified gel was dried at 80 °C under normal pressure for 18 h, and after pulverization and sieving, TMCS-modified hydrophobic SiO2 aerogel powder with a particle size D50 of 5 μm was obtained. Next, the sealing solution was prepared: KH550 was used as the film-forming silane, with a volume concentration of 6%. The volume ratio of ethanol to water in the solvent was 95:5. Acetic acid was used to adjust the pH to 4.5 and hydrolyzed for 2 hours. 8 wt.% of TMCS-modified SiO2 aerogel powder was added, and the mixture was mechanically stirred or ultrasonically dispersed until homogeneous. The sample with the deposited conductive layer was placed in the sealing solution and immersed at 25°C for 15 minutes, then pulled up at a speed of 2 cm / min. After that, it was pre-cured at 30°C for 12 minutes, then heated to 130°C at a heating rate of 5°C / min and held for 25 minutes. It was then cooled in the furnace and aged at room temperature for 24 hours to obtain the composite coating sample. Finally, the appearance of the sample was inspected. If a small amount of uncrosslinked floating layer was present on the surface, it was gently wiped away with a lint-free cloth moistened with anhydrous ethanol. The sample was then placed in a desiccator at room temperature for 24 hours to stabilize the coating.

[0060] Cross-sectional SEM measurements showed that the total thickness of the composite coating was approximately 18.9 μm, comprising a multi-element rare earth composite conversion film of approximately 1.6 μm, an MXene / Ag composite conductive network layer of approximately 5.3 μm, and a TMCS-modified hydrophobic SiO2 aerogel silane thermal barrier sealing layer of approximately 12.0 μm. The average Vickers microhardness of the sample obtained in this example was 104 HV0.1; the adhesion grade tested using the cross-cut adhesion test was 0; the electromagnetic shielding effectiveness was measured to be 108 dB when the composite magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300 °C was approximately 8.5 h; the neutral salt spray test duration was approximately 1150 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 5.3 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.12 mm / a.

[0061] Example 2

[0062] A heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8.5Al-4Si-1.2Ca-0.6Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were then hot-extruded at 350℃ at a speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0063] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0064] A multi-element rare earth composite conversion membrane was prepared. The nucleation solution was prepared with Ce(NO3)3·6H2O 0.020 mol / L, La(NO3)3·6H2O 0.040 mol / L, Sm(NO3)3·6H2O 0.010 mol / L, phytic acid 4 mL / L, and H2O 26 mL / L, adjusted to pH 5.0. The stabilizing solution was prepared with Y(NO3)3·6H2O 0.010 mol / L, Na2MoO4·2H2O 5 g / L, NH4H2PO4 10 g / L, NaVO3 1.0 g / L, K2ZrF6 1.5 g / L, and BTA 0.5 g / L, adjusted to pH 4.2. The pretreated sample was immersed in the nucleation solution for 5 min, then in the stabilizing solution for 10 min to form a multi-element rare earth composite conversion membrane on the substrate surface. The sample was then placed in a 5.0% NH4H2PO4 solution and densified at 50°C for 4 minutes. After removal, it was cleaned and dried.

[0065] Prepare the MXene / Ag composite conductive network layer. First, take 1g of Ti3AlC2 and add it to an etching system prepared with 1.5g of LiF and 30mL of 9mol / L HCl. Etch at 40℃ with magnetic stirring for 36h. After etching, repeatedly centrifuge and wash with deionized water until the pH of the supernatant is about 6. Then, redisperse the precipitate in deionized water, sonicate on ice for 75min, and collect the supernatant after low-speed centrifugation to obtain Ti3C2T. x MXene dispersion. 0.5 g of MXene dispersion was added to 100 mL of an ethanol / water mixture with a volume ratio of 90:10. 1.5 g of KH550 was slowly added dropwise, and the mixture was refluxed at 60 °C for 6 h. After centrifugation and washing until neutral, the mixture was freeze-dried under vacuum to obtain KH550-MXene. Separately, 100 mL of a 0.02 mol / L AgNO3 ethanol / water solution was prepared, and 0.5 g of PVP was added. A 0.04 mol / L ascorbic acid solution was added dropwise with stirring, and the mixture was reacted for 30 min to obtain Ag sol. DDT ethanol solution was then added, controlling the DDT:Ag mass ratio at 0.10:1, and the mixture was stirred at room temperature for 8 h. After centrifugation, washing, and vacuum drying, DDT-Ag was obtained. Weigh 0.064 g of KH550-MXene and 0.016 g of DDT-Ag, disperse them in 100 mL of ethanol / water with a volume ratio of 90:10, add 0.01 g of PVP, and sonicate for 40 min to obtain the electrophoresis solution; use the sample as the cathode and the graphite plate as the anode, with an electrode spacing of 15 mm, and deposit for 10 min under a DC voltage of 30 V, with a magnetic stirring speed of 200 rpm during the deposition process; after deposition, take out the sample, gently rinse with ethanol, and dry at 70 °C for 40 min.

[0066] A thermal barrier sealing layer of TMCS-modified hydrophobic SiO2 aerogel was prepared. A mixture of TEOS, ethanol, and water at a volume ratio of 1:4:2.5 was prepared. Hydrolysis was performed by adjusting the pH to 3 with hydrochloric acid, followed by polycondensation by adjusting the pH to 9 with ammonia. The mixture was stirred at room temperature for 1.2 h to obtain a SiO2 sol. The sol was allowed to stand for 12 h to gel, then aged for 36 h. The sol was replaced three times with anhydrous ethanol, each time for 12 h. The sol was then modified in a 10% TMCS / n-hexane mixture at 60℃ for 12 h. After drying at 80℃ under normal pressure for 18 h, the sol was pulverized and sieved to obtain TMCS-modified hydrophobic SiO2 aerogel powder with a D50 of 5 μm. A sealing solution was prepared using ethanol / water at a volume concentration of 6% KH550 and a volume ratio of 95:5. The pH was adjusted to 4.5 with acetic acid and hydrolyzed for 2 h. 8 wt.% of the TMCS-modified SiO2 aerogel powder was added and dispersed evenly. The sample with the deposited conductive layer was immersed at 25℃ for 15 min, pulled up at a speed of 2 cm / min, pre-cured at 30℃ for 12 min, then heated to 130℃ at a speed of 5℃ / min and held for 25 min, cooled in the furnace, and aged at room temperature for 24 h to obtain the composite coating sample. Finally, it was subjected to visual inspection and stabilization treatment by placing it in a desiccator at room temperature for 24 h.

[0067] Cross-sectional SEM measurements showed that the total thickness of the composite coating was approximately 19.4 μm, including a multi-element rare earth composite conversion film of approximately 1.9 μm, an MXene / Ag composite conductive network layer of approximately 6.3 μm, and a TMCS-modified hydrophobic SiO2 aerogel silane thermal barrier sealing layer of approximately 11.2 μm. The average Vickers microhardness of the sample obtained in this example was 101 HV0.1; the adhesion grade tested using the cross-cut adhesion test was level 1; the electromagnetic shielding effectiveness was measured to be 96 dB when the composite magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300 °C was approximately 7.0 h; the neutral salt spray test duration was approximately 1020 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 8.8 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.18 mm / a.

[0068] Example 3

[0069] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 380℃ at an extrusion speed of 0.5 mm / s and an extrusion ratio of 9:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0070] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0071] Prepare a multi-element rare earth composite conversion membrane. The nucleus solution was prepared as follows: Ce(NO3)3·6H2O 0.020 mol / L, La(NO3)3·6H2O 0.040 mol / L, Sm(NO3)3·6H2O 0.010 mol / L, phytic acid 4 mL / L, H2O2 6 mL / L, adjusted to pH 5.0. The stabilizing solution was prepared as follows: Y(NO3)3·6H2O 0.010 mol / L, Na2MoO4·2H2O 5 g / L, NH4H2PO4 10 g / L, NaVO3 1.0 g / L, K2ZrF6 1.5 g / L, BTA 0.5 g / L, adjusted to pH 4.2. The pretreated sample was first immersed in the nucleation solution for 5 minutes, and then immersed in the stabilizing solution for 10 minutes to form a multi-element rare earth composite conversion film; then it was densified in 5.0% NH4H2PO4 solution at 50℃ for 4 minutes, and then washed and dried.

[0072] Prepare an MXene / Ag composite conductive network layer. Take 1 g of Ti3AlC2 and add it to an etching system prepared with 1.5 g of LiF and 30 mL of 9 mol / L HCl. Etch at 40 °C for 36 h. Wash with deionized water until the pH of the supernatant is approximately 6. After redispersing, ultrasonically peel off under ice bath conditions for 75 min. Centrifuge at low speed to obtain the supernatant to obtain Ti3C2T. xMXene dispersion. Take 0.5 g of the MXene dispersion and add it to 100 mL of ethanol / water (90:10 v / v). Slowly add 1.5 g of KH550 and reflux at 60 °C for 6 h. Centrifuge, wash until neutral, and freeze-dry under vacuum to obtain KH550-MXene. Separately, take 100 mL of 0.02 mol / L AgNO3 ethanol / water solution, add 0.5 g of PVP, and reduce with 0.04 mol / L ascorbic acid solution for 30 min to obtain Ag sol. Add DDT ethanol solution, controlling the DDT:Ag ratio to 0.10:1, and react at room temperature for 8 h. Centrifuge, wash, and freeze-dry to obtain DDT-Ag. Weigh 0.064 g of KH550-MXene and 0.016 g of DDT-Ag, disperse them in 100 mL of ethanol / water at a ratio of 90:10 (volume ratio), add 0.01 g of PVP, and sonicate for 40 min to obtain the electrophoresis solution; use the sample as the cathode and the graphite plate as the anode, with an electrode spacing of 15 mm, and deposit at 30 V for 10 min, stirring magnetically at 200 rpm during the deposition process; after deposition, rinse with ethanol and dry at 70 °C for 40 min.

[0073] A thermal barrier sealing layer of TMCS-modified hydrophobic SiO2 aerogel was prepared. A mixture of TEOS, ethanol, and water at a volume ratio of 1:4:2.5 was used. Hydrolysis was performed by adjusting the pH to 3 with hydrochloric acid, followed by polycondensation by adjusting the pH to 9 with ammonia. The mixture was stirred at room temperature for 1.2 h to obtain a homogeneous SiO2 sol. The sol was allowed to stand for 12 h to gel, then aged for 36 h. Ethanol was replaced three times, 12 h each time. The sol was then modified in a 10% TMCS / n-hexane mixture at 60℃ for 12 h. After drying at 80℃ under normal pressure for 18 h, the sol was pulverized and sieved to obtain TMCS-modified hydrophobic SiO2 aerogel powder with a D50 of 5 μm. A sealing solution was prepared using ethanol / water at a volume concentration of 6% KH550 and a volume ratio of 95:5. The pH was adjusted to 4.5 with acetic acid, and the solution was hydrolyzed at room temperature for 2 h. 8 wt.% of the aerogel powder was then added and dispersed evenly. The sample with the deposited conductive layer was immersed at 25℃ for 15 min and then pulled up at 2 cm / min; it was pre-cured at 30℃ for 12 min, then heated to 130℃ at 5℃ / min and held for 25 min, cooled in the furnace, and aged at room temperature for 24 h to obtain the composite coating sample. Finally, the sample was visually inspected and placed in a desiccator at room temperature for 24 h.

[0074] Cross-sectional SEM measurements showed that the total thickness of the composite coating was approximately 18.3 μm, comprising a multi-element rare-earth composite conversion film of approximately 1.6 μm, an MXene / Ag composite conductive network layer of approximately 5.2 μm, and a TMCS-modified hydrophobic SiO2 aerogel silane thermal barrier sealing layer of approximately 11.5 μm. The average Vickers microhardness of the sample obtained in this example was 97 HV0.1; the adhesion grade tested using the cross-cut adhesion test was level 1; the electromagnetic shielding effectiveness was measured to be 95 dB when the composite magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300 °C was approximately 6.5 h; the neutral salt spray test duration was approximately 960 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 12.8 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.26 mm / a.

[0075] Example 4

[0076] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 350℃ at an extrusion speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0077] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0078] A multi-element rare earth composite conversion membrane was prepared. The nucleation solution was prepared with Ce(NO3)3·6H2O 0.025 mol / L, La(NO3)3·6H2O 0.050 mol / L, Sm(NO3)3·6H2O 0.012 mol / L, phytic acid 5 mL / L, and H2O 28 mL / L, adjusted to pH 4.8. The stabilizing solution was prepared with Y(NO3)3·6H2O 0.015 mol / L, Na2MoO4·2H2O 6 g / L, NH4H2PO4 12 g / L, NaVO3 1.5 g / L, K2ZrF 6 2.0 g / L, and BTA 0.6 g / L, adjusted to pH 4.0. The pretreated sample was first immersed in the nucleation solution for 6 min, then immersed in the stabilizing solution for 8 min to form the multi-element rare earth composite conversion membrane. The sample was placed in a 5 wt.% mixed phosphate solution and densified at 50°C for 5 min. After removal, it was cleaned and dried.

[0079] Prepare the MXene / Ag composite conductive network layer. First, take 1g of Ti3AlC2 and add it to an etching system prepared with 1.5g of LiF and 30mL of 9mol / L HCl. Etch at 40℃ with magnetic stirring for 36h. After etching, wash repeatedly with deionized water until the pH of the supernatant is about 6. Then, ultrasonically peel off under ice bath conditions for 75min. Centrifuge at low speed to collect the supernatant to obtain Ti3C2T x MXene dispersion. Take the dispersion containing 0.5 g of MXene and add it to 100 mL of ethanol / water with a volume ratio of 90:10. Slowly add 1.5 g of KH550, reflux at 60 °C for 6 h, centrifuge and wash until neutral, then freeze-dry under vacuum to obtain KH550-MXene. Separately prepare 100 mL of 0.02 mol / L AgNO3 ethanol / water solution, add 0.5 g of PVP, and reduce with 0.04 mol / L ascorbic acid solution for 30 min to obtain Ag sol; then add DDT ethanol solution, controlling the DDT:Ag ratio to 0.10:1, and react at room temperature for 8 h; centrifuge, wash, and vacuum dry to obtain DDT-Ag. Weigh KH550-MXene and DDT-Ag to a mass ratio of 7:3, prepare an electrophoresis buffer with a total complex concentration of 0.9 g / L, an ethanol:deionized water volume ratio of 90:10, add 0.01 g of PVP, and sonicate for 40 min. Using the sample as the cathode and the graphite plate as the anode, with an electrode spacing of 15 mm, a DC voltage of 30 V was applied for deposition for 10 min. During the deposition process, the sample was magnetically stirred at 200 rpm. After deposition, the sample was removed, gently rinsed with ethanol, and dried at 70 °C for 40 min.

[0080] A TMCS-modified hydrophobic SiO2 aerogel thermal barrier sealing layer was prepared. A mixture of TEOS, ethanol, and water at a volume ratio of 1:4:2.5 was used. Hydrolysis was performed by adjusting the pH to 3 with hydrochloric acid, followed by polycondensation by adjusting the pH to 9 with ammonia. The mixture was stirred at room temperature for 1.2 h to obtain a homogeneous SiO2 sol. The sol was allowed to stand for 12 h to gel, then aged for 36 h. The sol was then replaced three times with anhydrous ethanol, each time for 12 h. Finally, the sol was modified in a 10% TMCS / n-hexane mixture at 60℃ for 12 h. After drying at 80℃ under normal pressure for 18 h, the sol was pulverized and sieved to obtain TMCS-modified hydrophobic SiO2 aerogel powder with a particle size D50 of 10 μm. A sealing solution was prepared using ethanol / water at a volume concentration of 6% KH550 and a volume ratio of 95:5. The pH was adjusted to 4.5 with acetic acid and hydrolyzed for 2 h. 9 wt.% of the TMCS-modified SiO2 aerogel powder was added and dispersed evenly. The sample with the deposited conductive layer was immersed at 25℃ for 15 min, pulled up at a speed of 2 cm / min, pre-cured at 30℃ for 10 min, then heated to 130℃ at a speed of 5℃ / min and held for 25 min, cooled in the furnace, and aged at room temperature for 24 h to obtain the composite coating sample. Finally, a visual inspection was performed, and the coating was placed in a desiccator for 24 h to stabilize it.

[0081] Cross-sectional SEM measurements showed that the total thickness of the composite coating was approximately 18.9 μm, including a multi-element rare earth composite conversion film of approximately 1.2 μm, an MXene / Ag composite conductive network layer of approximately 6.0 μm, and a TMCS-modified hydrophobic SiO2 aerogel silane thermal barrier sealing layer of approximately 11.7 μm. The average Vickers microhardness of the sample obtained in this example was 98 HV0.1; the adhesion grade tested using the cross-cut adhesion test was level 1; the electromagnetic shielding effectiveness was measured to be 102 dB when the composite magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300 °C was approximately 6.1 h; the neutral salt spray test duration was approximately 980 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 6.8 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.14 mm / a.

[0082] Comparative Example 1

[0083] Magnesium alloy ingots were prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). After obtaining the ingots by electric arc melting, the ingots were directly machined into samples with a thickness of 1 mm. No homogenization treatment, hot extrusion treatment, solution-aging heat treatment, degreasing, pickling, activation, rare earth conversion film treatment, MXene / Ag conductive network layer deposition, or TMCS-modified SiO2 aerogel thermal barrier sealing treatment were performed.

[0084] The average Vickers microhardness of the samples obtained in this comparative example was 78 HV0.1; the electromagnetic shielding effectiveness was measured to be 63 dB when the magnesium alloy plate thickness was 1 mm and the magnetic frequency was 1 GHz; the neutral salt spray test duration was approximately 10 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 150.0 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 3.20 mm / a.

[0085] Comparative Example 2

[0086] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). After obtaining ingots by arc melting, the ingots were homogenized at 450℃ and held for 22 hours before being air-cooled to below 300℃. The homogenized ingots were then hot-extruded at 350℃ at an extrusion speed of 0.7 mm / s and an extrusion ratio of 16:1. After hot extrusion, no solution treatment or aging treatment was performed, nor were subsequent degreasing, pickling, activation, rare earth conversion coating treatment, MXene / Ag conductive network layer deposition, or TMCS-modified SiO2 aerogel thermal barrier sealing treatment; the comparative sample was obtained directly.

[0087] The average Vickers microhardness of the samples obtained in this comparative example was 69 HV0.1; the electromagnetic shielding effectiveness was measured to be 65 dB when the magnesium alloy plate thickness was 1 mm and the magnetic frequency was 1 GHz; the neutral salt spray test duration was approximately 16 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 120.0 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 2.50 mm / a.

[0088] Comparative Example 3

[0089] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 350℃ at an extrusion speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0090] This comparative example only prepared magnesium alloy substrates after homogenization, hot extrusion, and solution-aging treatment, without subsequent degreasing, pickling, activation, rare earth conversion film treatment, MXene / Ag conductive network layer deposition, and TMCS-modified SiO2 aerogel thermal barrier sealing treatment.

[0091] The average Vickers microhardness of the samples obtained in this comparative example was 108 HV0.1; the electromagnetic shielding effectiveness was measured to be 76 dB when the magnesium alloy plate thickness was 1 mm and the magnetic frequency was 1 GHz; the neutral salt spray test duration was approximately 38 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 80.0 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 1.60 mm / a.

[0092] Comparative Example 4

[0093] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 350℃ at an extrusion speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0094] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0095] A multi-element rare earth composite conversion membrane was prepared. The nucleus solution was prepared with the following components: Ce(NO3)3·6H2O 0.020 mol / L, La(NO3)3·6H2O 0.040 mol / L, Sm(NO3)3·6H2O 0.010 mol / L, phytic acid 4 mL / L, and H2O 2 6 mL / L, adjusted to pH 5.0. The stabilizing solution was prepared with the following components: Y(NO3)3·6H2O 0.010 mol / L, Na2MoO4·2H2O 5 g / L, NH4H2PO4 10 g / L, NaVO3 1.0 g / L, K2ZrF6 1.5 g / L, and BTA 0.5 g / L, adjusted to pH 4.2. The sample was first immersed in the nucleation solution for 5 min, and then in the stabilizing solution for 10 min to form a multi-element rare earth composite conversion film. The sample was then placed in a 5.0% (w / w) NH4H2PO4 solution and densified at 50°C for 4 min, followed by cleaning and drying. No further MXene / Ag composite conductive network layer deposition or TMCS-modified SiO2 aerogel thermal barrier sealing treatment was performed.

[0096] Cross-sectional SEM measurements showed that the thickness of the multi-element rare-earth composite conversion film obtained in this comparative example was approximately 1.7 μm. The average Vickers microhardness of the sample obtained in this comparative example was 103 HV0.1; the adhesion grade tested using the cross-cut adhesion test was level 2; the electromagnetic shielding effectiveness was measured to be 85 dB when the magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300℃ was approximately 2.0 h; the duration of the neutral salt spray test was approximately 180 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 23.0 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.50 mm / a.

[0097] Comparative Example 5

[0098] Heat-resistant magnesium alloy matrix was prepared according to the nominal composition Mg-8Al-3Si-2Ca-1Zn (wt.%). Ingots were obtained by arc melting, and the resulting ingots were homogenized at 450℃, held at that temperature for 22 h, and then furnace-cooled to below 300℃ and air-cooled. The homogenized ingots were hot-extruded at 350℃ at an extrusion speed of 0.7 mm / s and an extrusion ratio of 16:1. The hot-extruded samples were solution-treated at 450℃ for 2 h, water-quenched, and then aged at 175℃ for 36 h, followed by air cooling to room temperature.

[0099] The samples, after hot extrusion and heat treatment, underwent surface pretreatment. First, they were immersed in an alkaline degreasing solution at 55℃ for 8 minutes. The degreasing solution contained 25 g / L NaOH, 15 g / L Na3PO4, and 10 g / L Na2SiO3. After degreasing, they were rinsed with deionized water. Then, the samples were acid-washed in a 10% (w / w) HNO3 solution for 60 seconds. After rinsing, they were activated in a mixed activation solution containing 30 mL / L H3PO4 and 20 mL / L HF for 50 seconds. After removal, they were rinsed again and dried with cold air.

[0100] A multi-element rare earth composite conversion membrane was prepared. The nucleus solution was prepared with: Ce(NO3)3·6H2O 0.020 mol / L, La(NO3)3·6H2O 0.040 mol / L, Sm(NO3)3·6H2O 0.010 mol / L, phytic acid 4 mL / L, and H2O 2 6 mL / L, adjusted to pH 5.0. The stabilizing solution was prepared with: Y(NO3)3·6H2O 0.010 mol / L, Na2MoO4·2H2O 5 g / L, NH4H2PO4 10 g / L, NaVO3 1.0 g / L, K2ZrF6 1.5 g / L, and BTA 0.5 g / L, adjusted to pH 4.2. The pretreated sample was first immersed in the nucleation solution for 5 minutes, and then immersed in the stabilizing solution for 10 minutes to form a multi-element rare earth composite conversion film; then it was densified in a 5.0% NH4H2PO4 solution at 50°C for 4 minutes, and then washed and dried.

[0101] Prepare an MXene / Ag composite conductive network layer. Take 1 g of Ti3AlC2 and add it to an etching system prepared with 1.5 g of LiF and 30 mL of 9 mol / L HCl. Etch at 40 °C with magnetic stirring for 36 h. Wash repeatedly with deionized water by centrifugation until the pH of the supernatant is approximately 6. Then, ultrasonically peel off under ice bath conditions for 75 min. Centrifuge at low speed to collect the supernatant to obtain Ti3C2T. x MXene dispersion. A dispersion containing 0.5 g of MXene was added to 100 mL of ethanol / water at a volume ratio of 9:1. 1.5 g of KH550 was slowly added dropwise, and the mixture was refluxed at 60 °C for 6 h. After centrifugation and washing until neutral, the mixture was freeze-dried under vacuum to obtain KH550-MXene. Separately, 100 mL of 0.02 mol / L AgNO3 ethanol / water solution was prepared, and 0.5 g of PVP was added. Under stirring, 0.04 mol / L ascorbic acid solution was added dropwise for reduction for 30 min to obtain Ag sol. Then, DDT ethanol solution was added dropwise, controlling the DDT:Ag ratio at 0.10:1, and the mixture was reacted at room temperature for 8 h. After centrifugation, washing, and vacuum drying, DDT-Ag was obtained. Weigh 0.064 g of KH550-MXene and 0.016 g of DDT-Ag, disperse them in 100 mL of ethanol / water with a volume ratio of 90:10, add 0.01 g of PVP, and sonicate for 40 min to prepare the electrophoresis solution. Using the sample as the cathode and a graphite plate as the anode, with an electrode spacing of 15 mm, apply a 30 V DC voltage for deposition for 10 min. During deposition, use magnetic stirring at 200 rpm. After deposition, rinse with ethanol and dry at 70 °C for 40 min. No further TMCS-modified SiO2 aerogel thermal barrier sealing treatment is performed.

[0102] Cross-sectional SEM measurements showed that the total thickness of the composite layer was approximately 6.7 μm, with the multi-element rare earth composite conversion film thickness at approximately 1.5 μm and the MXene / Ag composite conductive network layer thickness at approximately 5.2 μm. The average Vickers microhardness of the sample obtained in this comparative example was 97 HV0.1; the adhesion rating tested using the cross-cut adhesion test was Grade 1; the electromagnetic shielding effectiveness was measured to be 98 dB when the magnesium alloy sheet thickness was 1 mm and the magnetic frequency was 1 GHz; the heat resistance time at 300℃ was approximately 3.5 h; the neutral salt spray test duration was approximately 420 h; and the self-corrosion current density in a 3.5 wt.% NaCl solution at room temperature was approximately 13.6 μA / cm². 2 The corrosion rate calculated by the immersion corrosion weight loss method is approximately 0.30 mm / a.

[0103] Table 1. Summary of performance data for Examples 1-4 and Comparative Examples 1-5

[0104] Example 1 104 Level 0 108 8.5 1150 5.3 0.12 Full processing technology Example 2 101 Level 1 96 7.0 1020 8.8 0.18 Full processing technology Example 3 97 Level 1 95 6.5 960 12.8 0.26 Full processing technology Example 4 98 Level 1 102 6.1 980 6.8 0.14 Full processing technology Comparative Example 1 78 -- 63 -- 10 150.0 3.20 Magnesium alloy ingots Comparative Example 2 69 -- 65 -- 16 120.0 2.50 Extruded magnesium alloy ingots Comparative Example 3 108 -- 76 -- 38 80.0 1.60 Magnesium alloy ingots after extrusion and heat treatment Comparative Example 4 103 Level 2 85 2.0 180 23.0 0.50 Extrusion + Heat Treatment + Multi-element Rare Earth Conversion Membrane Comparative Example 5 97 Level 1 98 3.5 420 13.6 0.30 Extrusion + Heat treatment + Multi-element rare earth conversion film + MXene / Ag electromagnetic shielding layer

[0105] As can be seen from the test results of Examples 1-4 and Comparative Examples 1-5, the multi-level synergistic technical route of "matrix structure regulation - multi-element rare earth composite conversion film - MXene / Ag composite conductive network layer - TMCS - modified hydrophobic SiO2 aerogel thermal barrier sealing layer" proposed in this invention can significantly improve the comprehensive service performance of magnesium alloys.

[0106] First, as shown in Comparative Examples 1, 2, and 3, while using only the optimal alloy composition, homogenization and hot extrusion, or further solution-aging heat treatment can improve the matrix structure and increase hardness to some extent, the improvement in corrosion resistance, electromagnetic shielding performance, and high-temperature protection performance remains limited. Comparative Example 1, without any treatment, exhibited the most severe corrosion, with the highest self-corrosion current density and corrosion rate, and the shortest salt spray life. Comparative Example 2 indicates that homogenization and hot extrusion alone improved the matrix structure, but the improvement in corrosion resistance and shielding performance was relatively small due to the lack of an effective functional layer on the surface. Comparative Example 3 further illustrates that while homogenization, hot extrusion, and solution-aging treatment can significantly improve matrix hardness and structural stability, without the subsequent construction of a composite functional layer on the surface, it is still difficult to meet the requirements for high corrosion resistance, high electromagnetic shielding, and high-temperature service.

[0107] Secondly, as shown in Comparative Example 4, after further constructing a multi-element rare earth composite conversion film on the surface of the magnesium alloy substrate after homogenization, hot extrusion, and solution-aging treatment, the corrosion resistance, adhesion, and electromagnetic shielding ability of the sample were significantly improved compared to Comparative Examples 1-3. This indicates that the Ce / La / Sm ternary rare earth-phytic acid nucleation layer and the Y-Mo-PV-Zr-BTA multi-component synergistic stabilizing layer can form a relatively dense and stable interface layer on the magnesium alloy surface, enhancing the chemical bonding and mechanical interlocking of the film / substrate interface, and effectively reducing the rate of diffusion of corrosive media into the substrate. However, with only the conversion film, the conductive pathway has not yet been established, and the thermal barrier layer has not been formed. Therefore, its electromagnetic shielding performance and high-temperature protection performance are still significantly insufficient.

[0108] Furthermore, as shown in Comparative Example 5, the electromagnetic shielding effectiveness of the sample was significantly improved after constructing an MXene / Ag composite conductive network layer on the basis of the multi-element rare earth composite conversion film. This indicates that the conductive network formed by electrophoretic deposition after pre-modification of KH550-MXene and DDT-Ag can effectively construct a continuous conductive path and achieve efficient electromagnetic attenuation through conductivity loss, interface polarization, and multiple reflections. Meanwhile, the corrosion resistance and adhesion of Comparative Example 5 were also further improved compared to Comparative Example 4, indicating that the conductive network layer has a certain covering effect on surface defects. However, due to the lack of the outermost TMCS-modified hydrophobic SiO2 aerogel thermal barrier sealing layer, its heat resistance time, salt spray lifetime, and long-term impermeability protection capability are still lower than those of the complete composite system.

[0109] Furthermore, as shown in Examples 1-4, when a multi-element rare earth composite conversion film, an MXene / Ag composite conductive network layer, and a TMCS-modified hydrophobic SiO2 aerogel thermal barrier sealing layer are sequentially constructed on the basis of an optimally structured matrix, the resulting composite system exhibits excellent comprehensive performance in terms of hardness, adhesion, electromagnetic shielding, heat resistance, and corrosion resistance. Among them, Example 1, using the optimal alloy composition Mg-8Al-3Si-2Ca-1Zn and a complete set of optimal processing parameters, yielded the sample with the best comprehensive performance, indicating that the process combination corresponding to Example 1 is the preferred embodiment of the present invention.

[0110] In summary, the performance improvement of this invention does not stem from a single process step, but rather from the significant synergistic effect between various structural layers: the heat-resistant magnesium alloy substrate, after homogenization, hot extrusion, and solution-aging treatment, provides a stable microstructure conducive to nucleation for subsequent film layers; the multi-element rare earth composite conversion film improves the film / substrate interface bonding and provides primary corrosion resistance protection; the MXene / Ag composite conductive network layer significantly enhances electromagnetic shielding capabilities; and the TMCS-modified hydrophobic SiO2 aerogel thermal barrier sealing layer further enhances its thermal insulation, hydrophobic impermeability, and defect sealing functions. The synergistic effect of these four elements elevates the magnesium alloy from a traditional single-surface barrier protection system to a multi-level composite protection system that combines microstructural strengthening, interface stability, electromagnetic shielding, and thermal barrier isolation, demonstrating significant technological advancement and practical application value.

Claims

1. A method for preparing a magnesium alloy with synergistic enhancement of electromagnetic shielding and heat and corrosion resistance by matrix structure and conversion film, characterized in that, Includes the following steps: (1) Prepare magnesium alloy matrix Mg-8Al-3Si-2Ca-1Zn (wt.%), and perform homogenization treatment, low-speed hot extrusion, solution treatment and aging heat treatment; (2) After the magnesium alloy substrate is subjected to surface pretreatment of degreasing, pickling, activation and cleaning in sequence, a multi-element rare earth composite conversion film is prepared on the surface of the magnesium alloy substrate by step-by-step impregnation and then subjected to phosphate densification treatment: S2.1 The magnesium alloy substrate is placed in the nucleation solution and immersed for 2-8 min to form a synergistic nucleation layer containing Ce, La, Sm ternary rare earth elements and phytic acid. Then, it is immersed in the stabilizing solution for 5-15 min to form a multi-anion stabilizing layer containing synergistic Y-Mo-PV-Zr and benzotriazole (BTA). The nucleation solution contains: Ce(NO3)3·6H2O 0.010~0.030 mol / L, La(NO3)3·6H2O 0.020~0.060 mol / L, Sm(NO3)3·6H2O 0.005~0.015 mol / L, phytic acid 2~6 mL / L, H2O2 4~10 mL / L, and pH 4.5~5.5; The stabilizing solution contains: Y(NO3)3·6H2O 0.005~0.020mol / L, Na2MoO4·2H2O 2~8 g / L, NH4H2PO4 5~15 g / L, NaVO3 0.5~2 g / L, K2ZrF6 0.5~3 g / L, benzotriazole (BTA) 0.2~1g / L, and pH 3.5~5.0; S2.2 The phosphate densification treatment solution includes NH4H2PO4 and / or (NH4)2HPO4, with a mass concentration of 4.5% to 5.5%, a treatment temperature of 45 to 55°C, and a treatment time of 3 to 5 min; (3) An MXene / Ag composite conductive network layer was constructed on the densified magnesium alloy surface by electrophoretic deposition: S3.1 KH550 silane-modified MXene: Take Ti3C2T x The MXene dispersion was transferred to a mixed solvent of ethanol and deionized water at a volume ratio of 9:1, and γ-aminopropyltriethoxysilane (KH550) was slowly added dropwise. The mass ratio of KH550 to MXene was (1~5):

1. The mixture was then refluxed under magnetic stirring at 60~70℃ for 4~8 h, allowing KH550 to chemically bond with the -OH / -F end groups on the MXene surface through a hydrolysis-condensation reaction, forming KH550-MXene covalently grafted with aminosilane. After the reaction was completed, the mixture was centrifuged and washed until neutral, and then freeze-dried under vacuum to obtain KH550 silane-modified MXene powder. S3.2 DDT thiol-modified Ag nanoparticles: An ethanol solution of 1-dodecyl mercaptan (DDT) was added dropwise to Ag sol at a mass ratio of DDT to Ag of (0.05~0.20):

1. The mixture was stirred at room temperature for 4~12 h to allow DDT to be stably coated on the Ag surface through strong Ag-S coordination bonds, forming DDT-Ag. After centrifugation, washing, and vacuum drying, DDT thiol-modified Ag nanoparticles were obtained. S3.3 Electrophoretic Solution Preparation and Deposition: Weigh KH550-MXene and DDT-Ag at a mass ratio of (7~9):(3~1), disperse them in a mixed solvent of ethanol and deionized water with a volume ratio of 80:20~98:2, add 0.05~0.2 g / L PVP as a dispersion stabilizer, and sonicate to obtain a uniform and stable electrophoretic solution, wherein the total concentration of the KH550-MXene and DDT-Ag complex is 0.4~1.0 g / L; use the sample to be plated as the cathode and an inert electrode as the anode, and carry out electrochemical deposition at room temperature under magnetic stirring. After the electrochemical deposition is completed, take out the sample, rinse and dry it. (4) A silane sealing agent doped with TMCS-modified hydrophobic SiO2 aerogel is used to perform thermal barrier sealing treatment on the magnesium alloy after the conductive network layer is deposited, forming a heat insulation and protection top layer. S4.1: The hydrophobic SiO2 aerogel powder has a particle size D50 of 2~15 μm and is hydrophobically modified on the wet gel surface by trimethylchlorosilane. S4.2 Preparation of the sealing solution: KH550 is used as the film-forming silane with a volume concentration of 5% to 8%. A mixed solution of ethanol and water with a volume ratio of 90:10 to 98:2 is used as the solvent. The pH is adjusted to 4.0 to 5.5 with acetic acid and hydrolyzed for 1 to 3 hours. TMCS-modified hydrophobic SiO2 aerogel powder with a mass fraction of 5% to 12% is added to the solution. The mixture is mechanically stirred or ultrasonically dispersed for 20 to 60 minutes to form the sealing solution. S4.3 Impregnation and curing: Immerse the sample after depositing the conductive network layer into the sealing liquid, impregnate at 25~30℃ for 10~20 min, and pull it out at a uniform rate of 1~3 cm / min; after pre-curing at 30℃ for 8~15 min, raise the temperature to 120~140℃ at 3~7℃ / min and hold for 20~30 min, cool with the furnace, and age at room temperature for 20~28 h.

2. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, The magnesium alloy matrix contains 2-4 wt.% Si, 1-3 wt.% Ca, 7-9 wt.% Al, and 0.5-1.5 wt.% Zn, with the balance being Mg and unavoidable impurities.

3. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, In step (1), the homogenization treatment temperature is 440-460℃, and after holding at this temperature for 18-24 h, it is cooled in the furnace to below 300℃ and then air-cooled to room temperature. The low-speed hot extrusion rate is 0.5–1 mm / s, the hot extrusion temperature is 350–380℃, and the hot extrusion ratio is 9:1 or 16:

1. The solution treatment temperature is 440–460℃, and the solution is held for 1.5–3 hours before water quenching. The aging treatment temperature is 170-190℃, and the temperature is maintained for 30-40 hours before air cooling to room temperature.

4. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, In step (2), the nucleation solution contains Ce(NO3)3·6H2O at a concentration of 0.020 mol / L, La(NO3)3·6H2O at a concentration of 0.040 mol / L, Sm(NO3)3·6H2O at a concentration of 0.010 mol / L, phytic acid at a volume concentration of 4 mL / L, H2O2 at a volume concentration of 6 mL / L, pH 5.0, and an immersion time of 5 min. The stabilizing solution contained 0.010 mol / L Y(NO3)3·6H2O, 5 g / L Na2MoO4·2H2O, 10 g / L NH4H2PO4, 1.0 g / L NaVO3, 1.5 g / L K2ZrF6, and 0.5 g / L benzotriazole. The pH was 4.2, and the immersion time was 10 min. The phosphate densification solution was NH4H2PO4 with a mass concentration of 5%, the treatment temperature was 50℃, and the treatment time was 4 min.

5. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, In step S3.1, the mass ratio of KH550 to MXene is 3:1; the reaction is carried out under reflux with magnetic stirring at 60°C for 6 hours. In step S3.2, the mass ratio of DDT to Ag is 0.10:1, and the reaction is carried out at room temperature with stirring for 8 h. The Ag sol is prepared by using AgNO3 as the silver source, dissolving AgNO3 in an ethanol / water mixed solvent to prepare 0.01~0.05 mol / L Ag sol. + The solution was prepared by adding PVP as a dispersant and slowly adding ascorbic acid or NaBH4 as a reducing agent under stirring, with Ag:reducing agent = 1:(1~3), to prepare nano Ag sol with a particle size of 20~50 nm.

6. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, The Ti3C2T in S3.1 x The MXene dispersion was prepared by the following method: Using a corrosion-resistant polytetrafluoroethylene or polypropylene reaction vessel, LiF was added to a hydrochloric acid solution under magnetic stirring to prepare an in-situ fluorination etching system. The concentration of the hydrochloric acid was 8–10 mol / L, and the amount of LiF added was 1.0–2.0 g / 20 mL of hydrochloric acid solution. Subsequently, Ti3AlC2 powder was slowly added, controlling the mass ratio of Ti3AlC2 to LiF to be 1:(1.2–1.5). The reaction was stirred at 30–45 °C for 30–40 h to selectively remove the Al layer. After etching, the slurry is transferred to a centrifuge and repeatedly washed with deionized water at a speed of 4200–4800 rpm for 6–8 min per cycle, until the pH of the supernatant reaches 6–7. The resulting precipitate is then redispersed in deionized water and ultrasonically exfoliated under ice bath conditions for 70–80 min to obtain few-layer or monolayer Ti3C2T. x MXene dispersion; after separation, centrifuge again at low speed and collect the supernatant for later use.

7. The preparation method of the matrix-conversion film synergistic enhancement electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, In step S3.3, KH550-MXene and DDT-Ag are mixed in a mass ratio of 8:2; the total concentration of both in the electrophoresis buffer is 0.8 g / L, the concentration of PVP is 0.1 g / L, and the volume ratio of ethanol to deionized water is 90:

10. The electrode spacing is 12~20 mm, a DC voltage of 25~35 V is applied for deposition for 8~12 min, the deposition solution temperature is controlled at 23~27℃, and the liquid is kept uniform by magnetic stirring at 100~250 rpm during deposition. After deposition, the sample is taken out, the undeposited particles are gently rinsed with ethanol, and dried at 65~75℃ for 35~45 min. Preferably, the electrode spacing is 15 mm, a DC voltage of 30 V is applied for deposition for 10 min.

8. The method for preparing a matrix-conversion film synergistically enhanced electromagnetic shielding, heat-resistant and corrosion-resistant magnesium alloy according to claim 1, characterized in that, In step (4), the volume concentration of KH550 in the sealing solution is 6%, the volume ratio of ethanol to water is 95:5, the hydrolysis time is 2 h, the mass fraction of TMCS-modified SiO2 aerogel powder is 8%, the impregnation and curing conditions are: impregnation at 25℃ for 15 min, lifting rate is 2 cm / min, pre-curing at 30℃ for 12 min, then heating to 130℃ at 5℃ / min and holding for 25 min, cooling with furnace, and aging at room temperature for 24 h.

9. The preparation method of the matrix-conversion film synergistic enhancement of electromagnetic shielding and heat- and corrosion-resistant magnesium alloy according to claim 1, characterized in that, The TMCS-modified hydrophobic SiO2 aerogel described in S4.1 is prepared by the following method: using tetraethyl orthosilicate and / or water glass as the silicon source and anhydrous ethanol as the solvent, a homogeneous SiO2 sol is obtained by two-step catalytic hydrolysis-condensation with acid and base, and stirring at room temperature for 1~1.5 h; the sol is allowed to stand for 8~16 h to form a gel, and then aged for 24~48 h to enhance the strength of the skeleton. After the aged wet gel was replaced with anhydrous ethanol 1 to 3 times, it was immersed in a TMCS / n-hexane mixture to carry out a silanization replacement reaction of the surface silanol groups. The volume concentration of TMCS was 5% to 15%, the modification temperature was 50 to 70℃, and the modification time was 6 to 24 h. This caused a large number of -OH groups on the gel surface to be replaced by -OSi(CH3)3 to form a deep hydrophobic framework. The modified gel was dried at 60 to 100℃ under normal pressure for 12 to 24 h, pulverized and sieved to obtain TMCS-modified hydrophobic SiO2 aerogel powder with a particle size D50 of 2 to 15 μm.

10. The electromagnetic shielding, heat-resistant and corrosion-resistant magnesium alloy prepared by the method of preparing a matrix-conversion film synergistic enhancement electromagnetic shielding, heat-resistant and corrosion-resistant magnesium alloy according to any one of claims 1-9, characterized in that, Using Mg-8Al-3Si-2Ca-1Zn (wt.%) as the matrix, and the metallographic structure of the matrix being a heat-dissipating and stable Mg2Si and Al2Ca nanophase, the matrix surface consists of a Ce / La / Sm ternary rare earth + phytic acid nucleation layer, a Y-Mo-PV-Zr-BTA synergistic multi-anion stabilization layer, an MXene / Ag composite conductive network layer, and a thermal barrier protection top layer. The Ce / La / Sm ternary rare earth + phytic acid nucleation layer and the Y-Mo-PV-Zr-BTA synergistic multi-anion stabilization layer together constitute a multi-element rare earth composite conversion film. The thermal barrier protection top layer is formed by curing a silane sealing agent doped with TMCS-modified hydrophobic SiO2 aerogel.